Immune checkpoint inhibitor-induced takotsubo syndrome and diabetic ketoacidosis: rare reactions. Issue 2 (1st February 2021) - Oldfield, Kieran; Jayasinghe, Rohan; Niranjan, Selvanayagam; Chadha, Sameer
Abstract : Immune checkpoint inhibitors (ICIs) are increasingly used to treat certain malignancies due to their higher efficacy compared with conventional chemotherapy. As familiarity with these agents increases, it is becoming apparent that a significant number of patients treated with ICIs experience adverse events. With time, more immune-related adverse events (IRAEs) are being recognised. It is important to be vigilant for IRAEs and recognise that a patient may have multiple IRAEs affecting multiple organ systems. Common cardiovascular adverse events associated with ICIs include myocarditis, arrhythmias and pericarditis. This case report identifies a patient presenting with takotsubo syndrome followed by ketoacidosis (associated with sodium-glucose transport protein 2 (SGLT2) inhibitor) in the setting of combination ipilimumab and nivolumab therapy for metastatic melanoma.